Autosomal‐dominant early‐onset spastic paraparesis with brain calcification due to IFIH1 gain‐of‐function. Issue 8 (4th June 2018) - Ruaud, Lyse; Rice, Gillian I.; Cabrol, Christelle; Piard, Juliette; Rodero, Mathieu; van Eyk, Lien; Boucher‐Brischoux, Elise; de Noordhout, Alain Maertens; Maré, Ricardo; Scalais, Emmanuel; Pauly, Fernand; Debray, François‐Guillaume; et al.
Abstract: We describe progressive spastic paraparesis in two male siblings and the daughter of one of these individuals. Onset of disease occurred within the first decade, with stiffness and gait difficulties. Brisk deep tendon reflexes and extensor plantar responses were present, in the absence of intellectual disability or dermatological manifestations. Cerebral imaging identified intracranial calcification in all symptomatic family members. A marked upregulation of interferon‐stimulated gene transcripts was recorded in all three affected individuals and in two clinically unaffected relatives. A heterozygous IFIH1 c.2544T>G missense variant (p.Asp848Glu) segregated with interferon status. Although not highly conserved (CADD score 10.08 vs. MSC‐CADD score of 19.33) and predicted as benign by in silico algorithms, this variant is not present on publically available databases of control alleles, and expression of the D848E construct in HEK293T cells indicated that it confers a gain‐of‐function. This report illustrates, for the first time, the occurrence of autosomal‐dominant spastic paraplegia with intracranial calcifications due to an IFIH1 ‐related type 1 interferonopathy. Abstract : By describing a family where three individuals over two generations present progressive isolated spastic paraparesia, associated in one of them with extensive brain calcification on CT scan, we came to the conclusion that it relates to an IFIH1 ‐associated interferonopathy. Interestingly, prediction softwares were non‐contributive in establishing pathogenicity of the corresponding c.2445T>G missense variant, only demonstrated through a construct in HEK293T cells. Two relatives with a strong interferon signature were completely asymptomatic, illustrating how clinical expression can be highly variable in interferonopathies.